New Directions in Regional Economic Development - Karlsson, Charlie; Andersson, Ake E.; Cheshire, Paul C.; Stough, Roger R. (Advances in Spatial Science, The Regional Science Series, 2009)
The emphasis of this book lies on emerging hypotheses, new methods and theoretic developments in the field of regional economic development. A further amplification is provided with a diverse set of cases extending this new way of thinking at the theory and methods level into policy and practice. The case studies range from a focus on Europe, Central and East Asia and North America. Considerable emphasis is laid on the role of entrepreneurship and innovation as drivers of economic growth and development on the sub-national regional level.